Застосування наноматеріалу в ембріогенетичній системі in vitro отримання ембріонів свиней - Зюзюн, А.Б.; Щербак, О.В.; Осипчук, О.С.; Ковтун, С.І.; Дзіцюк, В.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. The optimization model culturing somatic and germ cells of animals through the use of nanomaterials currently is
an important task in the system of development and improvement of effective ways to get in vitro oocytes preimplantant
embryos and embryonic stem cells. Methods. To research the oocyte-cumulus complexes (OCC), pigs were divided into
two groups: the experimental group, in which cultivation was carried out in a medium containing 0.001 % concentration
of UFS / N-Gal and the control group, in which cultivation OCC conducted without the addition of nanomaterials.
Ejaculated cryopreserved sperm of boar was used for in vitro fertilization of pig’s oocytes. Results. Morphological and
cytogenetic analysis showed that the level of maturation of oocytes in vitro in the experimental group was 13.6 % higher
compared to the control group (70.6 % ± 3.6). To investigate the in vitro maturation of oocytes pigs spent their fertilization
of cryopreserved boar sperm. The quantity of zygotes in the experimental group was formed outside the body by 11.0 %
more than in the control group (31.8 % ± 4.9), also level splitting of embryos was higher at 15.1 % in the experimental
group compared with controls (18.2 % ± 4.1). Conclusion. The system of optimization in conditions of in vitro biological
activity of nanomaterials was developed and the methods of biotechnological manipulation of gametes females in the
system of rational use and reproduction of native breeds of farm animals were improved.
Keywords: oocytes, in vitro fertilization, embryos, nanomaterial, N-galactosamine, cytogenetic analysis.